The Effect of Expectation Confirmation and Perceived Usefulness on Continuance Intention of QRIS Mobile Banking Users: The Mediating Role of Customer Satisfaction - Rizka Alfiyaturrohmah; Mahelan Prabantarikso; Batara Maju Simatupang; Nuri Wulandari (Research and Community Service UNIVERSITAS KALBIS, 2026)
This research aims to test the influence of expectation confirmation and perceived usefulness on the continuance intention of QRIS mobile banking users mediated by customer satisfaction. The sample in this study were banking customers who were recorded as actively using QRIS services spread including Jakarta, West Java and East Java involving 300 respondents. The analysis technique used Structural Equation Modelling – Partial Least Squares analysis. The results of the research obtained: perceived usefulness, expectation confirmation, and customer satisfaction has a significant effect on continuance intention; expectation confirmation has an effect on customer satisfaction; and gender demographic factors (control variables) have a significant effect on continuance intention, whereas age and income factors are not significant. The managerial implication is that banking service providers in Indonesia can continue to innovate and develop QRIS, which is not only the development of QRIS MPM, QRIS CPM, and QRIS TTS, but can also answer business challenges and customer needs for QRIS mobile banking services that enable customers to conduct digital financial transactions across countries.